(untitled) (Nexo Revista Científica, 2022)
When developing canning technologies raw material processing processes thermophysical calculations are inevitably used. This work’s purpose is to analyze the tropical fruits thermophysical characteristics. The research objects were the following fruits: kiwi, papaya, avocado and figs. The stationary flat layer method was used to analyze the thermal conductivity. The cryoscopic temperature was determined by the thermogram flat surface which was obtained during the product freezing. The hydrostatic weighing method was used to determine the density. The sugar content was determined using the refractometric method. The moisture content was determined by drying-out to a constant mass. As a result of the carried out work, the physical and chemical parameters of kiwi, avocado, papaya and figs were determined. The thermophysical properties of tropical fruits such as heat capacity, cryoscopic temperature, thermal conductivity, and the amount of frozen moisture, were calculated.